(untitled) (Conference Zone, 2021)
In the modern educational system of military universities, a key factor reflecting the nature of the process of education and upbringing of cadets is a complex of formed competencies. General cultural, general professional and military-professional competencies are implemented through the knowledge gained, the skills to be taught and the skills formed, mainly in the process of conducting classroom studies and independent work of students. Requirements for results presented in the process of studying academic disciplines their mastering should underlie the teaching methods used by the teaching staff, be applied in orientation and reflect the level of training of cadets in a military specialty